SPINSMEDE: a transnational taining experience on soil protection - Figueiredo, Tomás de (2012)
SPinSMEDE, acronym of Soil Protection in Sloping Mediterranean Agri- Environments, an Erasmus Intensive Programme, funded by the EC Lifelong Learning Programme, was designed and implemented following the policy context of the Thematic Strategy for Soil Protection in Europe. This document announced expectable demand for technical competences to meet increased requirements on the issue, most needed to cope with the specific soil degradation problems of Mediterranean hill-slopes. SPinSMEDE took place during three years (2008-2010), in three different places (Portugal, Greece and Spain), involving students and lecturers from five Universities. The presentation aims at reporting this transnational training experience on soil protection. The design, implementation and evaluation phases are described, outlining the main background elements, methodological approaches and outcomes of each phase. Namely, context-driven justification of the project, a description of the partnership and programme contents are included in the design phase. Programme implementation is addressed in terms of students profile, activities performed, assessment requirements, support material provided, and project deliverables. After describing the programme evaluation procedures developed and applied, the discussion focus on SPinSMEDE success, drawbacks, and problems arose and ways adopted to cope with them. Final remarks state main lessons learned and and programme follow-up activities envisaged.